1B.09: ACCURACY OF HOME VERSUS AMBULATORY BLOOD PRESSURE MONITORING IN THE DIAGNOSIS OF WHITE-COAT AND MASKED HYPERTENSION. (June 2015) - Kang, Y.; Li, Y.; Huang, Q.F.; Song, J.; Shan, X.L.; Dou, Y.; Xu, X.J.; Chen, S.H.; Wang, J.G.
Abstract : Objective: We investigated accuracy of home blood pressure (BP) monitoring in the diagnosis of white-coat and masked hypertension in comparison with ambulatory BP monitoring. Design and method: Our study subjects were enrolled in the ongoing China Ambulatory and Home Blood Pressure Registry and underwent clinic, home and 24-hour ambulatory blood pressure measurements. The blood pressure threshold for hypertension diagnostic was 140mmHg and/or 90mmHg (systolic/diastolic) for clinic blood pressure, 130mmHg and/or 80mmHg for 24-hour ambulatory blood pressure and 135mmHg and/or 85mmHg for home blood pressure. We defined white-coat hypertension as an elevated clinic systolic/diastolic pressure and a normal 24-hour ambulatory or home systolic/diastolic pressure and masked hypertension as a normal clinic systolic/diastolic pressure and an elevated 24-hour ambulatory or home systolic/diastolic pressure. Results: In untreated subjects (n = 573), the prevalence of white-coat hypertension (13.1% vs. 19.9%), masked hypertension (17.8% vs. 13.1%) and sustained hypertension (46.4% vs. 39.6%) significantly (P < 0.02) differed between 24-hour ambulatory and home BP monitoring. In treated subjects (n = 1201), only the prevalence of masked hypertension differed significantly (18.7% vs.14.5%, P = 0.005). Regardless of the treatment status, home compared with 24-hour ambulatory BP had low sensitivity (range, 47%-74%) but high specificity (86%-94%) and accordingly low positive (41%-87%) but high negative predictive values (80%-94%), and had moderate diagnostic agreement (82%-85%) and Kappa statistic (0.41–0.66). In untreated and treated subjects, age advancing was associated with a higher prevalence of white-coat hypertension and a lower prevalence of masked hypertension defined by 24-hour ambulatory (P < 0.04) but not home BP (P > 0.10). Conclusions: Home BP monitoring has high specificity but low sensitivity in the diagnosis of white-coat and masked hypertension, and may therefore behave as a complementary to, but not a replacement of, ambulatory BP monitoring.